THE EFFECT OF ACUTE KIDNEY INJURY IN ELDERLY PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION - SAOOD , Y; SALMAN , A; KHAN , MI; YOUNIS, KA (Biological and Clinical Sciences Research Journal, 2023)
This study aims to determine the frequency of acute kidney injury (AKI) in patients who undergo percutaneous coronary intervention (PCI) and its impact on elderly patients. To achieve this, 80 patients admitted to Ayub Teaching Hospital from March 2019 to August 2020 for PCI were studied for AKI after the procedure. The primary endpoint was mortality from all causes, while the secondary was mortality due to major cardiovascular events. The results showed that out of the 80 patients, 29 developed AKI, with a higher incidence observed in the older age group. These patients reported a higher rate of congestive heart failure, increased C-reactive proteins, and an increased rate of major adverse cardiovascular events, which was 39.43%. Furthermore, all-cause mortality was higher in patients suffering from AKI. In conclusion, this study highlights that one-fourth of elderly patients undergoing PCI face a higher risk of AKI. Further research is required to mitigate the mortality and morbidity associated with AKI in this vulnerable group.